Occupation and tongue cancer in Nordic countries - Johanna Peltonen; Rayan Nikkilä; Ahmed Al-Samadi; Antti Mäkitie; Jan Ivar Martinsen; Kristina Kjaerheim; Elsebeth Lynge; Par Sparen; Laufey Tryggvadottir; Elisabete Weiderpass; Tuula Salo; Eero Pukkala (BMC, 2024)
Abstract Purpose Almost 200,000 tongue cancers were diagnosed worldwide in 2020. The aim of this study was to describe occupational risk variation in this malignancy. Methods The data are based on the Nordic Occupational Cancer (NOCCA) study containing 14.9 million people from the Nordic countries with 9020 tongue cancers diagnosed during 1961-2005. The standardized incidence ratio (SIR) of tongue cancer in each occupational category was calculated using national incidence rates as the reference. Results Among men, the incidence was statistically significantly elevated in waiters (SIR 4.36, 95% confidence interval (CI) 3.13--5.92), beverage workers (SIR 3.42, 95% CI 2.02-5.40), cooks and stewards (SIR 2.55, 95% CI 1.82-3.48), seamen (SIR 1.66, 95% CI 1.36-2.00), journalists (SIR 1.85, 95% CI 1.18-2.75), artistic workers (SIR 2.05, 95% CI 1.54-2.66), hairdressers (SIR 2.17, 95% CI 1.39-3.22), and economically inactive persons (SIR 1.57, 95% CI 1.42-1.73). Among women, the SIR was statistically significantly elevated only in waitresses (SIR 1.39, 95% CI 1.05-1.81). Statistically significant SIRs ≤ 0.63 were observed in male farmers, gardeners, forestry workers and teachers, and in female launderers. Conclusions These findings may be related to consumption of alcohol and tobacco, but the effect of carcinogenic exposure from work cannot be excluded.